2021
DOI: 10.2196/28262
|View full text |Cite
|
Sign up to set email alerts
|

Internet Search Activity of Young People With Mood Disorders Who Are Hospitalized for Suicidal Thoughts and Behaviors: Qualitative Study of Google Search Activity

Abstract: Background Little is known about the internet search activity of people with suicidal thoughts and behaviors (STBs). This data source has the potential to inform both clinical and public health efforts, such as suicide risk assessment and prevention. Objective We aimed to evaluate the internet search activity of suicidal young people to find evidence of suicidal ideation and behavioral health–related content. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Thirty-eight studies identified information needs related to treatment for depression. The top three information needs within this theme were treatment options and comparison between options (24 studies, 63.2%) [ 6 , 13 , 15 , 16 , 18 , 20 , 21 , 30 46 ], side effects of treatment (19 studies, 50.0%) [ 6 , 13 , 16 , 18 , 21 , 32 , 34 , 35 , 38 , 41 , 43 45 , 47 52 ], and effectiveness/benefits of treatments and expected outcomes (15 studies, 39.5%) [ 6 , 13 , 16 , 18 21 , 33 , 34 , 40 , 41 , 44 , 49 , 50 , 53 ]. Other information needs included general information on medication (14 studies, 36.8%) [ 15 , 16 , 18 , 20 , 31 , 35 , 37 , 44 , 45 , 47 , 53 56 ], appropriate use of medication (13 studies, 34.2%) [ 13 , 16 , 19 , 20 , 22 , 37 , 41 , 43 , 48 , 49 , 51 , 53 , 57 ], length of treatment (7 studies, 18.4%) [ 19 , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty-eight studies identified information needs related to treatment for depression. The top three information needs within this theme were treatment options and comparison between options (24 studies, 63.2%) [ 6 , 13 , 15 , 16 , 18 , 20 , 21 , 30 46 ], side effects of treatment (19 studies, 50.0%) [ 6 , 13 , 16 , 18 , 21 , 32 , 34 , 35 , 38 , 41 , 43 45 , 47 52 ], and effectiveness/benefits of treatments and expected outcomes (15 studies, 39.5%) [ 6 , 13 , 16 , 18 21 , 33 , 34 , 40 , 41 , 44 , 49 , 50 , 53 ]. Other information needs included general information on medication (14 studies, 36.8%) [ 15 , 16 , 18 , 20 , 31 , 35 , 37 , 44 , 45 , 47 , 53 56 ], appropriate use of medication (13 studies, 34.2%) [ 13 , 16 , 19 , 20 , 22 , 37 , 41 , 43 , 48 , 49 , 51 , 53 , 57 ], length of treatment (7 studies, 18.4%) [ 19 , …”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two studies identified information needs for general facts about depression. Within these studies, the most frequently identified specific needs were symptoms/signs of depression (15 studies, 46.9%) [ 7 , 15 , 16 , 18 , 30 , 35 37 , 42 , 45 , 47 , 50 , 59 61 ], general information on depression (13 studies, 40.6%) [ 15 , 16 , 18 , 30 , 39 , 44 , 49 , 52 , 56 , 59 , 61 63 ], diagnosis (11 studies, 34.4%) [ 13 , 21 , 31 , 32 , 34 , 35 , 38 , 45 , 47 , 55 , 58 ], and aetiology (10 studies, 31.3%) [ 6 , 13 , 16 , 18 , 31 , 35 , 37 , 41 , 47 , 61 ]. Other information needs within this theme included prognosis of depression (6 studies, 18.8%) [ 6 , 16 , 31 , 36 , 49 , 58 ], information on suicidal thoughts (4 studies, 12.5%) [ 16 , 37 , 42 , 64 ], prevalence of depression (3 studies, 9.4%) [ 18 , 35 , 47 ], recent research on depression (2 studies, 6.3%) [ 35 , 61 ], whether depression is normal (2 ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations